Dark Tetrad and the Dysfunctional Family Environment as Facilitators of the Consumption of Psychoactive Substances - Damjanović, Andrijana; Međedović, Janko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
The Dark Tetrad is a psychological concept that originally consisted of three empirically overlapping components, Machiavellianism, narcissism and psychopathy; finally, sadism is included in the description of dark traits as well. The aim of this study was to examine the relationship between the Dark Tetrad traits, unfavorable environmental environment during childhood, and consumption of psychoactive substances (CPS). The data were collected via an online survey, and the analyses were conducted on a sample of 239 respondents (55.65% female). The results showed that psychopathy is the most important predictor of CPS because it independently and positively predicted all examined types of psychoactive substances' consumption. Narcissism has shown an independent positive contribution in the prediction of cigarette and cannabis consumption, as well as the overall measure of substance use. Machiavellianism and sadism had positive correlations with some of the examined criteria, but not an independent contribution in the regression models; this means that the detected bivariate associations can be reduced to the relations between other dark traits and consumption of CPS, most likely psychopathy. No connections were found between the unfavorable environment and the criterion variables, neither the interactions between dark traits and the environment in the prediction of CPS. We discuss the implications of the findings, taking into account the limitations of the research itself.